2018
DOI: 10.1111/pce.13425
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of a pea apyrase enhances root system architecture and drought survival in Arabidopsis and soybean

Abstract: Ectoapyrases (ecto-NTPDases) function to decrease levels of extracellular ATP and ADP in animals and plants. Prior studies showed that ectopic expression of a pea ectoapyrase, psNTP9, enhanced growth in Arabidopsis seedlings and that the overexpression of the two Arabidopsis apyrases most closely related to psNTP9 enhanced auxin transport and growth in Arabidopsis. These results predicted that ectopic expression of psNTP9 could promote a more extensive root system architecture (RSA) in Arabidopsis. We confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 93 publications
5
34
0
Order By: Relevance
“…Root system architecture plays a crucial role in crop productivity 28,29,48 and high ambient temperature affects both primary and lateral root growth 26,27,30 . The phenotypic analyses show that seedlings display a general growth promotion including elongation of hypocotyls, petioles and roots, and thickening of hypocotyls in response to high ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Root system architecture plays a crucial role in crop productivity 28,29,48 and high ambient temperature affects both primary and lateral root growth 26,27,30 . The phenotypic analyses show that seedlings display a general growth promotion including elongation of hypocotyls, petioles and roots, and thickening of hypocotyls in response to high ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
“…High ambient temperature also affects root system architecture 26,27 , which is linked to crop yield 28,29 . In sunflower and cotton, elevated temperature increases lateral root length and number 27 .…”
mentioning
confidence: 99%
“…The first ectoapyrase used in these transformation studies was psNTP9, which Thomas et al [ 92 ] showed could promote phosphate uptake and leaf growth when it was expressed in Arabidopsis seedlings. More recent studies, which examined the effects of ectopically expressing psNTP9 on mature plants, showed that it improved phosphate uptake, leaf growth, root-system architecture, and seed yield in both Arabidopsis and soybean plants [ 93 ]. Genetic manipulation of ectoapyrase expression in Arabidopsis has been carried out in numerous other studies.…”
Section: Role Of Ca 2+ /Cam-activated Apyrase Imentioning
confidence: 99%
“…Besides the report of Veerappa et al [ 93 ] noted above, several other transformation studies have been used to explore the function of apyrases in crop plants. The overexpression of an endogenous apyrase in Lotus japonicus [ 96 ] promoted nodulation, and the suppression of the GS52 apyrase in soybean inhibited nodulation [ 97 ].…”
Section: Role Of Ca 2+ /Cam-activated Apyrase Imentioning
confidence: 99%
“…These authors consider the genomics approaches that have led to recent discoveries relating to adaptive genes in legumes. Individual mechanisms that allow survival of extremes of water availability are reported in several manuscripts.For example, the ectoapyrases, otherwise known as ecto-NTPDases that function to decrease levels of extracellular ATP and ADP are shown to be important in drought tolerance(Veerappa et al, 2018), as are the micro RNAs, miR398, and miR2119 in controlling superoxide dismutase and alcohol dehydrogenase mRNAs (De la Rosa,Covarrubus, & Reyes, 2018). The role of the alternative oxidase (AOX) in legumes in plant growth and performance is discussed in the paper bySweetman, Soole, Jenkins, and Day (2018).…”
mentioning
confidence: 99%